Population dynamics of bee colonies located in airborne contaminated regions - LIAKOS (Β. ΛΙΑΚΟΣ), V.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Effects of airborne contaminating (polluting) agents particularly Pb, on the population dynamics and brood rearing of bee colonies, were investigated. No significant differences were noted in the population dynamics and foraging habits of bees, between bee colonies located in urban areas with high levels of environmental pollutants and those situated in rural unburdened areas. Aerial pollutants at the City center hade high values, but they were lower than the upper accepted limits of the European Union. The lead (Pb) content of bee tissues, honey and pollen were found to be proportional to the location of the bee colonies, with significantly higher values recorded in urban areas. The same significant differences were noted in the Pb tissue content among foragers, domesticated bees, and larvae within the same colony. In urban areas the Pb tissue content was 4,05 ppm in 6-day old larvae, 5,90 in newly emerged bees, 8,80 in nurse bees and 6,80 in worker bees. On the contrary, the comparing values in rural areas were 1 ppm in 6- day old larvae, 1,90 in newly emerged bees, 1,90 in nurse bees and 0,70 in worker bees.